Investigating the Effect of Gradation, Temperature and Loading Duration on the Resilient Modulus of Asphalt Concrete - Muhammad Junaid; Muhammad Zafar Ali Shah; Ghulam Yaseen; Hammad Hussain Awan; Daud Khan; Muhammad Jawad (Civil Engineering Journal, 2022)
This research was carried out to assess the effect of aggregate skeleton, temperature variation, and loading duration on the resilient modulus of asphalt concrete mixtures. Two different gradation methods, i.e., the conventional method of gradation and the Bailey method of gradation, were adopted to design the aggregate skeleton. The effect of these gradation methods, with temperature and loading duration, on the resilient modulus of asphalt concrete has not been previously investigated. The Modified Marshall Test was used to determine optimum binder content against 4% air voids, and then volumetric and strength parameters were calculated against optimum binder content. For performance tests, specimens were prepared at optimum binder content using a Superpave gyratory compactor. An indirect tensile strength test on both types of mixtures was conducted, and a 20% value of indirect tensile strength was kept for peak load, whereas 10% was kept for seating load for conducting resilient modulus tests. The tests were conducted at 100 and 300 ms duration loads under two different temperatures, i.e., 25 oC and 40 oC. The results declared that aggregate skeleton, temperature, and loading duration have a prominent effect on the resilient modulus of asphalt concrete mixtures. Bailey gradation mixtures disclosed higher resilient modulus values than conventional gradation mixtures. Higher values of resilient modulus were observed for both gradation mixtures at low temperatures and under small duration loads than at high temperatures and large duration loads. The results of the two-way factorial design also confirmed the above findings. Doi: 10.28991/CEJ-2022-08-02-07 Full Text: PDF